Development of Cost-Effective Ultrasound Phantoms for Image Artifact Training: A Study on Learning Outcomes and Inter-Rater Agreement - NUR AQILA RAZALI; Sook Sam Leong (Journal of Clinical and Health Sciences, 2026)
PURPOSE: This study aimed to develop low-cost ultrasound phantoms for visualizing image artifacts in teaching and learning. METHOD: Four homemade phantoms were constructed using gelatin and corn flour. Different materials were used to replicate ultrasound artifacts: a stone for acoustic posterior shadowing, a water-filled glove for acoustic posterior enhancement, a glass mirror with a water-filled glove for the mirror artifact, and a PVC-insulated cable for the comet tail artifact. The phantoms were scanned, and images were analyzed by four sonographers to assess their reliability in visualizing artifacts. A group of students later scanned the phantoms to compare learning outcomes between theory-only and hands-on learning. RESULT: Mann-Whitney U test indicated that commercial phantoms had a significantly higher price (6.50) than the price of homemade phantoms (2.50), U = 16.000, p = 0.02. The Fleiss’ Kappa test showed a moderate agreement among four sonographers, k = 0.71 (p = < 0.001). The Mann-Whitney U test found no significant difference in marks scored by both groups, although the theory with hands-on learning group achieved higher scores (20.78) compared to the theory learning group (17.32), U = 139.000, p = 0.34. CONCLUSION: Homemade phantoms can serve as a cost-effective alternative to commercial phantoms for visualizing image artifacts in learning applications, demonstrating substantial agreement among sonographers. Thus, these phantoms offer an effective tool to enhance students' performance through hands-on practice.